Simulation of Mobile Robot Navigation System using Combination Method of A* Algorithm with Virtual Force Field - Harri Sapto Wijaya; Mitra Djamal (Institut Teknologi Bandung, 2007)
A novel mobile robot navigation system has been developed and simulated. This method took advantages of two known methods: A* algorithm for minimum path finding and Virtual Force Field (VFF) for obstacle avoidance. This method allow the dynamic of environment also semi fully informed map. A* and VFF had been combined by splitting the path which obtained by A* into several straight lines and a temporary target is putted on every turning point of straight lines for VFF method. Each time the temporary target is reached by robot, it will be deactivated and next temporary target will be activated, until the final target is reached. Simulation is run on MobotSim 1.0 software and the result shows that the robot could pass the U-like shape obstacle (which usually problem by just using VFF method), uninformed static obstacle, and uninformed moving obstacle.